1988
DOI: 10.2307/3314938
|View full text |Cite
|
Sign up to set email alerts
|

Patterned matrix derivatives

Abstract: A general procedure for obtaining matrix derivatives of functions of nonlinear patterned matrices is proposed. The method is extended to obtain the Jacobians of patterned matrix transformations. Nel (1980) and Wiens (1985) consider the linear patterned cases. The procedure proposed here takes care of these cases as well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…We must employ a careful strategy for taking derivatives with respect to a matrix if there are any elements in that matrix which are (possibly constant) functions of the other elements. Such an approach was developed in [70][71][72] and we summarize it here for a differentiable function G(A, A * ) of a complex patterned matrix A:…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We must employ a careful strategy for taking derivatives with respect to a matrix if there are any elements in that matrix which are (possibly constant) functions of the other elements. Such an approach was developed in [70][71][72] and we summarize it here for a differentiable function G(A, A * ) of a complex patterned matrix A:…”
Section: Discussionmentioning
confidence: 99%
“…In this appendix we recount the calculus of complex, patterned matrices developed in [47,[70][71][72] and summarized in [41]. This calculus was used in [41] to rigorously compute the derivative of a scalar function with respect to a Hermitian argument (20), and also provides a rigourous derivation of our result on patterned Hessians (36).…”
Section: Appendix B: Calculus Of Complex Patterned Matricesmentioning
confidence: 99%
“…First, we recount the calculus of complex, patterned matrices developed in [267,283,284,285] and summarized in [261]. This calculus was used in [261] to rigorously compute the derivative of a scalar function with respect to a Hermitian argument (6.19), and also provides a rigourous derivation of our result on patterned Hessians (6.36).…”
Section: When Is Patterned Matrix Calculus Required?mentioning
confidence: 99%
“…We must employ a careful strategy for taking derivatives with respect to a matrix if there are any elements in that matrix which are (possibly constant) functions of the other elements. Such an approach was developed in [283,284,285] and we summarize it here for a differentiable function G(A, A * ) of a complex patterned matrix A:…”
Section: Formal Calculus Of Complex Patterned Matricesmentioning
confidence: 99%
“…Tracy & Jinadasa (1988) [157] have shown that when we have one observation y t ∼ MV N(0, V t distribution the Fisher information matrix for the covariance matrix is I F (…”
Section: Expected Information Matrixmentioning
confidence: 99%